A hydrophilic nickel-zinc battery separator and a method of making the same

CN122889954APending Publication Date: 2026-10-09HUNAN KAINAFANG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610909763.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

随着循环次数增加,尖锐的枝晶可能刺穿隔膜,导致正负极直接接触,引发电池内部短路,严重时造成电池失效甚至安全事故

Benefits of technology

卓越的抗锌枝晶能力:得益于纳米ZrO2核的高模量与 LDH 壳层形成的迷宫效应,复合隔膜的穿刺强度显著提升,极大延长了电池的循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889954A_ABST
    Figure CN122889954A_ABST
Patent Text Reader

Abstract

The application provides a hydrophilic nickel-zinc battery diaphragm and a preparation method thereof, and belongs to the field of battery materials.The diaphragm is composed of a porous base film and a functional composite coating loaded on the surface.The coating uses imidazolium polymerized polybenzimidazole (PIL-PBI) as a cationic polymer matrix, and ZrO2@LDH core-shell heterojunction particles are uniformly dispersed in the coating.The scheme provides a high-hardness physical barrier by using ZrO2 cores to inhibit zinc dendrite puncture, and uses an in-situ grown two-dimensional layered double hydroxide (LDH) shell layer and the electrostatic repulsion effect of the cationic polymer to construct an "ion barrier" to cooperatively intercept zincate migration.The diaphragm prepared by the application has excellent alkaline stability, puncture strength and ion selectivity, can significantly prolong the cycle life of a nickel-zinc battery, and has important application value in the fields of high power and energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials, and particularly relates to a hydrophilic nickel-zinc battery separator and its preparation method. Background Technology

[0002] Nickel-zinc batteries, as an aqueous alkaline rechargeable battery, possess advantages such as high operating voltage, high specific energy, abundant raw materials, and environmental friendliness, showing broad application prospects in energy storage systems, power tools, and consumer electronics. The separator, as one of the key components of nickel-zinc batteries, functions to physically isolate the positive and negative electrodes to prevent internal short circuits, while also providing channels for ion transport in the electrolyte, directly affecting the battery's safety, cycle life, and rate performance. Nickel-zinc batteries typically use potassium hydroxide aqueous solution as the electrolyte; therefore, an ideal separator must possess good hydrophilicity to fully absorb the electrolyte, reduce membrane resistance, and also exhibit excellent mechanical strength, chemical stability, and thermal stability.

[0003] However, existing nickel-zinc battery separators face numerous technical challenges in practical applications. First, zinc dendrites, or zinc anodes, easily form on the zinc anode during charge-discharge cycles. With increasing cycle count, sharp dendrites can pierce the separator, causing direct contact between the positive and negative electrodes, leading to internal short circuits and, in severe cases, battery failure or even safety accidents. Second, discharge products from the zinc anode dissolve in alkaline electrolytes to form soluble zincate ions. These ions can migrate through the separator micropores to the positive electrode region under concentration gradients, where they are oxidized and precipitated on the positive electrode surface, causing irreversible loss of active material and electrode deformation, significantly reducing battery capacity retention and cycle life. Furthermore, to enhance the separator's physical barrier against dendrites, it is often necessary to increase the separator thickness or reduce porosity, but this increases ion transport resistance, leading to increased internal resistance and decreased rate performance. On the other hand, simple hydrophobic polyolefin separators are insufficient to meet the wetting requirements of alkaline electrolytes, while hydrophilic modification treatments may result in problems such as modified layer detachment or pore blockage. Therefore, how to effectively suppress zinc dendrite penetration and block zincate ion shuttle while ensuring low resistance and high ionic conductivity has become a key bottleneck restricting the development of nickel-zinc battery technology. Summary of the Invention

[0004] The first objective of this invention is to provide a hydrophilic battery separator, comprising: Porous base membrane; and A functional composite coating loaded on the surface of the porous base membrane, the functional composite coating being composed of a cationic polymer matrix and core-shell heterojunction particles dispersed therein; The core-shell heterojunction particles include a ZrO2 core and a two-dimensional layered double hydroxide shell grown in situ on the surface of the ceramic core. The particle size of the ZrO2 cores ranges from 10 to 100 nm; The double hydroxide shell contains divalent metal elements. and trivalent metal elements ,in, Selected from at least one of Mg, Zn, and Ni, Selected from at least one of Al and Fe; and the and The molar ratio is 2-4:1; the thickness of the double hydroxide shell is between 5-20 nm.

[0005] Preferably, the cationic polymer matrix is ​​imidazole-infused polybenzimidazole, and the degree of substitution of imidazole-infused polybenzimidazole is between 20% and 40%.

[0006] Preferably, the thickness of the functional composite coating is between 2 and 10 μm.

[0007] A second objective of this invention is to provide a method for preparing the aforementioned hydrophilic battery separator, comprising the following steps: S1, in situ co-precipitation of double hydroxide precursors is induced in a suspension of nano-ceramic particles to form a double hydroxide shell on the surface of the ceramic particles, thus obtaining core-shell heterojunction particles. S2, the cationic polymer is dissolved in an organic solvent, the core-shell heterojunction particles are added, and a uniform coating slurry is obtained by high-shear dispersion; S3, the slurry is coated onto the surface of the pretreated porous base membrane; S4, the coated base film is immersed in a coagulation bath for phase transformation, and after washing and drying, the hydrophilic battery separator is obtained.

[0008] Preferably, in step S1, the nano-ceramic particles are surface activated by a silane coupling agent before co-precipitation; The coprecipitation process is carried out at 60-80°C, and the pH of the reaction system is maintained between 9.0 and 11.0. After co-precipitation is completed, in-situ aging treatment is required for 6-24 hours.

[0009] Preferably, in step S2, the organic solvent is selected from at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; The high-shear dispersion is performed at a rotation speed of 2000-5000 rpm.

[0010] Preferably, in step S2, the slurry further contains a dispersant with a mass fraction of 0.1-2%.

[0011] Preferably, in step S3, the pretreatment includes plasma treatment, corona treatment, or surfactant impregnation of the porous base membrane to reduce the wetting angle of the porous base membrane surface to below 30°.

[0012] Preferably, in step S4, the coagulation bath is a mixed solution of deionized water and ethanol, wherein the volume percentage of ethanol is 10-30%; the phase inversion time is 1-10 minutes, and the drying is carried out in a vacuum environment at 50-80°C.

[0013] A third objective of the present invention is to provide a nickel-zinc battery comprising a positive electrode, a zinc negative electrode, an electrolyte, and a hydrophilic battery separator as described above.

[0014] This invention solves the core bottleneck of zinc dendrite penetration and zincate migration in nickel-zinc batteries through a "three-level synergistic defense mechanism": (1) Microscopic “rigid and flexible” core-shell defense: using high-hardness nano ZrO2 as the core to provide the membrane with extremely high local mechanical strength, physically suppressing the linear growth of zinc dendrites.

[0015] Two-dimensional layered double hydroxides (LDHs) grown in situ on the surface of ZrO2 possess unique interlayer ion exchange capabilities. Due to the positive charge of their layers, they can chemically chelate and electrostatically adsorb the bulky zincate ions Zn(OH)4. 2- Capture or confine within its interlayer structure.

[0016] (2) The "charge fence" effect at the molecular level: Using imidazolium-ionized polybenzimidazole (PIL-PBI) as a matrix, the densely distributed positive charge centers (imidazolium cations) on its main chain and side chains construct an "electron fence" across the entire membrane. Based on the Donnan repulsion principle, this fence exhibits strong Coulomb repulsion against zincate ions with the same charge, while allowing smaller OH- ions to pass through. - The process was smooth, enabling precise ion sieving.

[0017] (3) Macroscopic “conformal coating” structure: Through phase inversion, PIL-PBI polymer forms a uniform conformal coating on the surface of the microporous base film and the internal fibers. This structure increases the tortuosity of the pores without blocking the original ion transport channels, further increasing the physical difficulty of zinc dendrite penetration.

[0018] This solution has the following significant beneficial effects: Excellent resistance to zinc dendrite formation: Thanks to the high modulus of the nano ZrO2 core and the labyrinth effect formed by the LDH shell, the puncture strength of the composite separator is significantly improved, greatly extending the cycle life of the battery.

[0019] Highly efficient zincate migration inhibition rate: Through the dual effects of chemical capture by LDH and electrostatic repulsion by cationic polymers, the loss of negative electrode active material to positive electrode is effectively prevented, the electrochemical activity of positive electrode is maintained, and the rapid decay of battery capacity is alleviated.

[0020] Excellent alkali stability and hydrophilicity: Using intrinsically alkali-resistant PBI as the modified matrix avoids the degradation risk of traditional quaternized polymers in strongly alkaline environments. Simultaneously, the LDH shell possesses natural superhydrophilicity, and combined with the pretreatment process of the base membrane, it allows the electrolyte to rapidly wet the separator, reducing battery internal resistance and improving high-current discharge performance.

[0021] Excellent interfacial adhesion: Because LDH is grown in situ on the ZrO2 surface, and there are strong hydrogen bonds and electrostatic interactions between PIL-PBI and inorganic particles, the functional coating adheres firmly to the substrate. Under long-term charge-discharge cycles and electrolyte erosion, the coating is not prone to peeling or particle detachment, ensuring the long-term stability of battery performance. Attached Figure Description

[0022] Figure 1 The image shows a SEM image of the hydrophilic battery separator prepared for serial number 1 in Table 1. Detailed Implementation

[0023] To better understand the present invention, the present invention will be further described below with reference to specific serial numbers. The terminology used in the serial numbers is for describing specific embodiments and does not constitute a limitation on the scope of protection of the present invention.

[0024] In the specific implementation methods, unless otherwise specified, the experimental methods used are all conventional methods, and the materials and reagents used are all commercially available unless otherwise specified.

[0025] Unless otherwise specified, percentages, % and so on in the specific implementation method are assumed to be mass percentages.

[0026] The particle size range of ZrO2 used in this invention is between 10-100 nm; The imidazolium-substituted polybenzimidazole (PIL-PBI) used in this invention has two specifications with imidazolium substitution degrees of 22% and 38%.

[0027] Example 1: Preparation of ZrO2-Mg-Al core-shell heterojunction particles, including the following steps: S1, take 10 parts by weight of ZrO2, add 10 times (w:v) of 95% ethanol water (pH pre-adjusted to 5.0 and containing 0.2 parts by weight of KH-550 coupling agent); stir at 70℃ for 4 hours, then wash and dry to obtain activated ZrO2 particles; S2, take 20 times (W:V) of deionized water for ZrO2 particles; mix and ultrasonically disperse for 30 min to form a uniform suspension; S3: Take 6.1 parts by mass of MgCl2·6H2O and 2.4 parts by mass of AlCl3·6H2O (Mg / Al molar ratio 3:1); add dropwise to the suspension, complete the dropwise addition within 2 hours, maintain the temperature at 65℃, and age in situ for 12 hours after the dropwise addition is completed; During the dropwise addition process, the mixed alkaline solution was continuously added to maintain the pH of the system at 10.0±0.5 (the mixed alkaline solution consisted of 2 mol / L NaOH and 1 mol / L Na2CO3).

[0028] S4: After aging, the system is centrifuged and the solid is collected; the solid is washed with deionized water until neutral, dried under vacuum at 60°C, and then ground to obtain ZrO2-Mg-Al core-shell heterojunction particles.

[0029] Example 2: Preparation of ZrO2-Zn-Al core-shell heterojunction particles, including the following steps: S1, same as in Example 1; S2, same as in Example 1; S3: Take 3.63 parts by mass of ZnCl2 and 2.4 parts by mass of AlCl3·6H2O (Zn / Al molar ratio 2:1); add dropwise to the suspension, complete the dropwise addition within 2 hours, maintain the temperature at 60℃, and age in situ for 12 hours after the dropwise addition is completed; During the dropwise addition process, the mixed alkaline solution was continuously added to maintain the pH of the system at 9.0±0.1 (the mixed alkaline solution consisted of 2 mol / L NaOH and 1 mol / L Na2CO3).

[0030] S4: Same as Example 1; ZrO2-Zn-Al core-shell heterojunction particles were obtained.

[0031] Example 3: Preparation of ZrO2-Ni-Fe core-shell heterojunction particles, including the following steps: S1, same as in Example 1; S2, same as in Example 1; S3: Take 9.51 parts by mass of NiCl2·6H2O and 2.70 parts by mass of FeCl3·6H2O (Ni / Fe molar ratio 4:1); add dropwise to the suspension (add 0.05 parts by mass of ascorbic acid to the suspension), complete the dropwise addition within 2 hours, maintain the temperature at 80℃, and age in situ for 12 hours after the dropwise addition is completed; During the dripping process, the mixed alkaline solution was continuously added to maintain the pH of the system at 11.0±0.5 (the mixed alkaline solution consisted of 2 mol / L NaOH and 1 mol / L Na2CO3).

[0032] S4: Same as Example 1; ZrO2-Ni-Fe core-shell heterojunction particles were obtained.

[0033] Example 4: Preparation of physically blended ZrO2-Mg-Al particles, comprising the following steps: S1: Take 6.1 parts by mass of MgCl2·6H2O and 2.4 parts by mass of AlCl3·6H2O (Mg / Al molar ratio 3:1); add dropwise to 20 times (w / v) of deionized water, complete the dropwise addition within 2 hours, maintain the temperature at 65℃, and age in situ for 12 hours after the dropwise addition is completed; During the dropwise addition process, the mixed alkaline solution was continuously added to maintain the pH of the system at 10.0±0.5 (the mixed alkaline solution consisted of 2 mol / L NaOH and 1 mol / L Na2CO3).

[0034] S2: After aging, the system is centrifuged and the solid is collected; the solid is washed with deionized water until neutral, dried under vacuum at 60°C, and then ground to obtain Mg-Al powder. 8.5 parts by mass of the Mg-Al powder and 10 parts by mass of unactivated ZrO2 particles are mechanically ground and mixed in a mortar for 30 minutes to obtain physically blended ZrO2-Mg-Al particles.

[0035] Example 5: Preparation of a hydrophilic battery separator, comprising the following steps; S1, according to the proportions in Table 1 below, take the corresponding mass parts of the main resin, functional filler, dispersant (polyvinylpyrrolidone, PVP K30) and solvent. S2, add PIL-PBI particles to the solvent and stir magnetically at 80°C for 6 hours until completely dissolved to form a transparent amber solution.

[0036] S3, add the functional filler and dispersant to the solution in S2, and shear disperse for 1 hour with the parameters shown in Table 1; then ball mill for 2 hours to obtain the coating slurry; S4. Select the porous base film (pretreated by plasma) shown in Table 1, place the porous base film on a glass plate, and use a wire bar coater to uniformly coat the slurry; set the wet film thickness to 20-30 μm. After being exposed to air for 30 seconds, it is quickly immersed in a coagulation bath.

[0037] The coagulation bath consists of a 20% volume fraction of ethanol aqueous solution.

[0038] Soak in deionized water for 24 hours to remove residual solvent, and finally vacuum dry at 60°C for 5 hours.

[0039] Table 1

[0040] Table 1 (continued)

[0041] In Table 1, the indicators for functional fillers, main resins, solvents, and polyvinylpyrrolidone are the amount added (parts by mass); for porous base membranes, “√” indicates that the corresponding porous base membrane is used, and “×” indicates that it is not used; the shear rate refers to the rotational speed during shear dispersion in step S3.

[0042] The performance of the samples prepared in Table 1 was tested, and the specific test items were as follows: 1. Contact Angle Test: The test method is the seated drop method in GB / T 24368-2009, "Measuring Contact Angle of Hydrophobic Contaminants on Glass Surface".

[0043] 2. Area Specific Resistance (ASR) test, the test method is SJ / T 10171-2016 General Test Method for Basic Performance of Alkaline Battery Separators.

[0044] 3. Zinc dendrite penetration resistance test (Time to Short-circuit) was conducted using the "constant current chronopotential method," the specific method of which is as follows: Electrode construction: A symmetrical battery structure using ZnI separator + electrolyte is adopted.

[0045] Electrolyte: Use a 6 mol / L KOH solution saturated with ZnO (to simulate the actual battery environment).

[0046] Constant current deposition: A constant current density (10 mA / cm²) is applied to a symmetrical cell, causing zinc to dissolve on one electrode and grow in dendrite form on the other electrode and advance into the separator.

[0047] Failure determination: Real-time monitoring of the battery's voltage-time curve.

[0048] Initial state: The voltage is at a relatively stable plateau.

[0049] Short circuit moment: When the dendrite pierces the diaphragm and comes into contact with the opposite electrode, the voltage will suddenly drop (close to 0V).

[0050] Data recording: The time from the start of power-on to the sudden voltage drop is called the "short-circuit induction time". The longer the time, the stronger the resistance to dendrite formation.

[0051] The results are shown in Table 2.

[0052] Table 2

[0053] As shown in Table 2, the data from Examples 1-3 and Comparative Examples 4, 9, and 10 demonstrate that the ZrO2@LDH core-shell heterojunction filler prepared by the in-situ co-precipitation method has significant implications for improving the overall performance of the diaphragm.

[0054] The core-shell structure is not a simple superposition of components, but rather the formation of an LDH shell with anion-trapping capability on the surface of hard ZrO2 particles, creating a continuous and smooth ion migration channel at the interface between the filler and the polymer matrix. Measured data show that the sheet resistivity of Example 1 is only 0.42 Ω·cm², far lower than that of the physical blend group (No. 4) and the single filler group (No. 9). This demonstrates that the heterojunction interface can effectively reduce the transport resistance of electrolyte ions, overcoming the technical pain point of traditional inorganic fillers easily agglomerating and blocking ion channels.

[0055] Regarding hydrophilic modification, this invention utilizes the synergistic effect of imidazole-onylened polybenzimidazole (PIL-PBI) and heterojunction fillers to achieve a qualitative leap in the membrane's wetting performance. A comparison of the contact angle data from Examples 1 and 5 with Comparative Examples 6 and 10 shows that the ionic properties of the PIL groups, combined with the abundant hydroxyl groups and capillary structure on the filler surface, cause the electrolyte contact angle to plummet from 84.1° of conventional PP membranes to below 20°, and even reach 13.1° after increasing the degree of substitution. This excellent hydrophilicity ensures rapid penetration and uniform distribution of the electrolyte within the membrane, fundamentally solving the "starved electrolyte" failure problem in alkaline batteries during charging and discharging, and providing a material basis for high-rate charging and discharging.

[0056] The diaphragm described in this invention exhibits excellent performance in suppressing zinc dendrite penetration. Zinc dendrite penetration resistance experiments show that the short-circuit induction time of Example 1 is as long as 480 min, an improvement of approximately 433% compared to the blank control group (serial number 10). This improvement is attributed to the strong mechanical support provided by the ZrO2 core and the regulating effect of the LDH shell on the interfacial charge distribution; both synergistically induce uniform zinc deposition, blocking the dendrite growth path from both physical and chemical dimensions. Furthermore, by adjusting the filler ratio and base film type (as in Examples 7 and 8), a balance can be further achieved between extremely low surface resistivity and ultra-long anti-penetration time.

[0057] In addition, scanning electron microscopy was performed on item 1 in Table 1 of Example 5, such as... Figure 1As shown, the ZrO2@LDH nanofiller (in the form of burr-like particles) with core-shell structure is uniformly dispersed and tightly coated on the surface of the polymer (PIL-PBI) fiber without obvious agglomeration.

[0058] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

Claims

1. A hydrophilic battery separator, characterized in that, include: Porous base membrane; as well as A functional composite coating loaded on the surface of the porous base membrane, the functional composite coating being composed of a cationic polymer matrix and core-shell heterojunction particles dispersed therein; The core-shell heterojunction particles include a ZrO2 core and a two-dimensional layered double hydroxide shell grown in situ on the surface of the ceramic core. The particle size of the ZrO2 cores ranges from 10 to 100 nm; The double hydroxide shell contains divalent metal elements. and trivalent metal elements ,in, Selected from at least one of Mg, Zn, and Ni, Selected from at least one of Al and Fe; and the and The molar ratio is 2-4:1; the thickness of the double hydroxide shell is between 5-20 nm.

2. The hydrophilic battery separator according to claim 1, characterized in that, The cationic polymer matrix is ​​imidazole-infused polybenzimidazole, with a degree of substitution between 20% and 40%.

3. The hydrophilic battery separator according to claim 1, characterized in that, The thickness of the functional composite coating is between 2 and 10 μm.

4. The method for preparing the hydrophilic battery separator according to any one of claims 1-3, characterized in that, Includes the following steps: S1, in situ co-precipitation of double hydroxide precursors is induced in a suspension of nano-ceramic particles to form a double hydroxide shell on the surface of the ceramic particles, thus obtaining core-shell heterojunction particles. S2, the cationic polymer is dissolved in an organic solvent, the core-shell heterojunction particles are added, and a uniform coating slurry is obtained by high-shear dispersion; S3, the slurry is coated onto the surface of the pretreated porous base membrane; S4, the coated base film is immersed in a coagulation bath for phase transformation, and after washing and drying, the hydrophilic battery separator is obtained.

5. The method for preparing the hydrophilic battery separator according to claim 4, characterized in that, In step S1, the nano-ceramic particles are surface activated by a silane coupling agent before co-precipitation. The coprecipitation process is carried out at 60-80°C, and the pH of the reaction system is maintained between 9.0 and 11.

0. After co-precipitation is completed, in-situ aging treatment is required for 6-24 hours.

6. The method for preparing the hydrophilic battery separator according to claim 4, characterized in that, In step S2, the organic solvent is selected from at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; The high-shear dispersion is performed at a rotation speed of 2000-5000 rpm.

7. The method for preparing the hydrophilic battery separator according to claim 4, characterized in that, In step S2, the slurry also contains a dispersant with a mass fraction of 0.1-2%.

8. The method for preparing the hydrophilic battery separator according to claim 4, characterized in that, In step S3, the pretreatment includes plasma treatment, corona treatment, or surfactant impregnation of the porous base membrane to reduce the wetting angle of the porous base membrane surface to below 30°.

9. The method for preparing the hydrophilic battery separator according to claim 4, characterized in that, In step S4, the coagulation bath is a mixed solution of deionized water and ethanol, wherein the volume percentage of ethanol is 10-30%; the phase inversion time is 1-10 minutes, and the drying is carried out in a vacuum environment at 50-80°C.

10. A nickel-zinc battery, characterized in that, It includes a positive electrode, a zinc negative electrode, an electrolyte, and a hydrophilic battery separator as described in any one of claims 1-3.